Manejo do solo para o cultivo de soja em terras baixas - Coelho, Lucas Lopes (2022)
Soybean cultivation in rotation with irrigated rice is an important alternative in the seek for economic sustainability in lowland areas. However, the characteristics of poor drainage and high compaction of these soils result in frequent periods of water stress to the plants. As a result, important metabolic processes can be affected, such as nitrogen biological fixation and photosynthetic rate. The use of mechanical soil management and cover crops may be an important strategy in the seek for a crop with greater yield stability. A two-year study was carried out in an Albaqualf, at the growing-seasons 2019/20 and 2020/21. The results generated three papers, which aimed to: verify the effect of mechanical soil management and seeder mechanisms on the quality of seed distribution and the initial establishment of soybean plants (chapter I); to determine the energy consumption of decompaction and the efficiency of mechanical management and use of Italian ryegrass in mitigating soil physical problems for soybean cultivation in lowlands (Chapter II); to evaluate soil management, Italian ryegrass cultivation and use of fertilizer deposition mechanisms in the seeder on soybean development in lowland areas (Chapter III). The experiment consisted of a 6x2 bifactorial. Factor A levels were implanted in the 2019/20 crop season, consisting of soil management in the off-season and fertilizer deposition mechanisms of a seeder-fertilizer: (A1) no soil preparation (NSP)+double disc (DD); (A2) NSP+chisel (CH) not aligned; (A3) NSP+CH+soil accommodation mechanism (SAM); (A4) scarified+DD; (A5) disc harrow+DD and (A6) chisel tillage+DD. Factor D was implemented prior to soybean harvesting in the first year of the study, consisting of ryegrass cultivation in the off-season (D1) and fallow (D2). In the 2020/21 crop season, the Scarified in 2020+DD treatment was added, while the disc harrow+DD management was suppressed. The SAM associated with the CH promotes better quality of depth seed distribution, in addition, the rupture of the compacted layer proved to be crucial in the establishment of an adequate initial stand of plants. In the seeder, the CH reduces the resistance to mechanical penetration (MP) of the soil in the crop row, however, it increases the energy consumption of the tractor when compared to the DD. Among the off-season managements, scarification, despite the low operational capacity, improves the physical parameters of the soil in the row and between the crop rows (MP and macroporosity), being part of these improvements noticeable for at least 15 months after the intervention. In plant development, NSP+DD management reduces root growth, photosynthetic capacity and soybean grain yield when compared to other treatments. The Italian ryegrass in a single crop does not influence the processes of re-accommodation of soil particles, as well as the soybean grains yield.